Clark Coolidge’s The Land of All Time: An Affectively Restless Ecopoem - Siltanen Elina; Guimarães João Paulo (Lodz University Press, 2025)
Clark Coolidge (1939–) is often connected with language poetry and the New York School. The language of his poetry is opaque and disjunctive, like that of the artists associated with the first group, but it is also energetic, rambling and fast-paced. Curiously, in his most recent book, The Land of All Time (2020), Coolidge displays ecological preoccupations, the first poem in the collection, “Goodbye,” asking us to reflect upon how nature and culture are today nearly indistinguishable: “hark! an ocean as / generator see the wires? me neither oh well / there’s a heat vent somewhere in this wilderness.” In this article, we explore how Coolidge mobilizes his extreme wordiness for ecological purposes, arguing that Coolidge’s The Land of All Time proposes a model for harnessing restless affect for responding to climate change and ecological crises in a way that allows for the exploration of possibilities rather than falling prey to environmental despair. Coolidge is interested in experimenting with how to respond to extreme situations with vibrancy, speed, and flow, aligning the dynamism of language with that of nature.